Literatur Review: Analisis Rasio Profitabilitas dan Rasio Likuiditas untuk Menilai Kinerja Keuangan - Mutmainah, Wita; Noviyanti, Shintia Rahma; Siregar, Arisa Juliana; Khaerunnisa, Khaerunnisa; Septiani, Anisa Septiani (Jurnal Disrupsi Bisnis, 2024)
This research discusses the analysis of profitability ratios and liquidity ratios to assess financial performance. Research is really needed because calculating ratios is really needed by a company, namely to determine the good and bad performance of a company's financial management. This research uses a literature review method with data and 5 scientific journals that have been reviewed. Based on the results of the analysis of profitability ratios and liquidity ratios to assess financial performance, the analysis of profitability ratios and liquidity ratios shows that the financial performance obtained from these two ratios, overall profitability performance shows good value and satisfactory results, because it is below the industry average and Financial performance is important because it can help measure the efficiency of financial management, support the decision-making process, facilitate future predictions, and enable performance comparisons with other companies in the same industrial sector. By understanding the significance of profitability ratios and liquidity ratios in the context of financial performance, this information can be used as a basis for decision making and evaluating company performance as well as to see the good and bad conditions of financial management by the company and as information on investment considerations in a company's shares.